Activating Effect of Benzbromarone, a Uricosuric Drug, on Peroxisome Proliferator-Activated Receptors. (23rd August 2007) - Kunishima, Chiyoko; Inoue, Ikuo; Oikawa, Toshihiro; Nakajima, Hiromu; Komoda, Tsugikazu; Katayama, Shigehiro
Abstract : Benzbromarone, a uricosuric drug, reportedly causes hepatic hypertrophy accompanied by proliferation of peroxisomes in rats. To elucidate the mechanisms underlying induction of peroxisome proliferation by benzbromarone, we examined binding affinity for peroxisome proliferator-activated receptorα (PPAR α ) andγ (PPAR γ ), and effects on the binding activity of PPARs with peroxisome proliferation-responsive element (PPRE) and expression of the PPARs target protein. Binding affinity of benzbromarone forPPAR α andPPAR γ was examined by reporter gene assay. Binding activity of PPARs with PPRE was determined by electric mobility shift assay, and expression of lipoprotein lipase (LPL) and acyl-CoA synthetase (ACS) by Western blot method. Benzbromarone displayed affinity forPPAR α andPPAR γ, and promoted binding of PPARs to PPRE. Furthermore, cultured cells with benzbromarone added showed upregulated expression of LPL and ACS. These results suggest that benzbromarone induces peroxisome proliferation in hepatocytes by binding to PPARs, and controls expression of proteins related to lipid metabolism.